African American children in early childhood education - Iruka, Iheoma U.; Curenton, Stephanie M.; Durden, Tonia R. (Bingley : Emerald Publishing Limited, 2017)
Approximately 45% of young black children in the United States (under the age of six) live in poverty. It is well documented that education and economic security are inextricably linked and that early learning and early reading are undisputed contributors to a successful education. This book presents both the challenges and opportunities that exist for addressing the critical needs of black children, who have been historically underserved in the U.S. education system. This book explores the language, cognitive, social-emotional, and health development of black children from birth to age 8. The chapters approach this in three ways; first, they tackle why it is problematic to only characterize Black children's accomplishment in terms of academic achievement. Second, they discuss the importance of the home-school environment connection. Lastly, they discuss the changes that need to be in teacher preparation in order to ensure that the workforce can practice racial equity in the classroom. These issues are woven together by a call to close the education opportunity gap via'equity adjustments' that can target educational and health disparities facing the black community.
Prelims -- Striving for educational equity -- Home and school environmental contexts -- Preparing teachers and improving practice -- About the Authors -- Index.
Includes bibliographical references and index.
Keywords: Education -- Multicultural Education; Multicultural education; African Americans -- Education (Early childhood) -- United States